Enhancing the provision of livestock marketing information in Somaliland - Mugunieri, Lawrence Godiah; Baker, Derek; Elmi, I.I.; Costagli, Riccardo; Gulaid, Ibrahim; Wanyoike, Francis N. (International Livestock Research Institute, 2014)
The economy of Somaliland depends on livestock, which employs about 70% of the population and contributes approximately 60% of GDP and 85% of export earnings. The principal export markets are the Kingdom of Saudi Arabia, Yemen, Oman, Egypt and the United Arab Emirates. Exports to these markets have shown a steady growth in the last four years. Despite recent growth in export volumes, livestock trade takes place in an environment characterized by an underdeveloped legal framework, contract uncertainty and high information costs among other factors. Trade is guided by informal traditional institutions, customs and religious practices that serve as alternatives to formal contracting. The Livestock Marketing Information System (LMIS) was initiated in 2007 to address the constraint of high market information cost. The purpose of the LMIS is to provide timely current information to livestock producers, traders, government officials and other development partners. It collects and disseminates data from three livestock markets (Hargeisa, Burao and Tog Wajaale), the port of Berbera and crossborder market of Lowya Caddo. It is implemented by the Somaliland Chamber of Commerce, Industries and Agriculture, in collaboration with the Ministry of Livestock, Ministry of Commerce, Ministry of Finance, the municipalities of Hargeisa, Burao and Tog Wajaale, with the technical support of Terra Nuova and funding from Danish Government. Although several agricultural market information systems exist in developing countries, the validity, reliability and impact of information they generate vary and depend on a number of factors. Some of these include technology used, technical capability of personnel, protocol employed in data capturing, management and transmission among others. Despite the Somaliland LMIS being in operation for eight year, there has been no attempt to evaluate its validity and reliability. To redress this concern, this study provides an appraisal of the validity of the Somaliland LMIS as a decision making tool for stakeholders, identifies its strengths and weaknesses and offers recommendations for improvement. The validity of the system was assessed by focussing on three areas. First, by evaluating the proportion of total Somaliland livestock exports that are traded through the monitored markets. This enabled understand how the LMIS covers the target population. Second, by analysing the extent to which the trends in volumes of livestock traded in monitored markets is explained by shocks and opportunities in both local and international markets; and third by evaluating the type of trends that exist in livestock prices and the main drivers of these trends. Data used were obtained from the LMIS database, comprising weekly traded volumes, weekly price data for different grades of small ruminants, cattle and camels, and weekly export trader numbers for a period 2007–12. The study shows that the LMIS has provided valid data and information over time, noting that the data series exhibited direct and strong relations with shocks and opportunities that have occurred in local and international markets. The LMIS’s coverage has been high and consistent for small ruminants, although modest for cattle and camels. A vector autoregressive model applied to quantify the effects of seasonal and occasional factors on price revealed that whereas prices of small ruminants and camels have exhibited secular and upwards trends over time, those of cattle have remained the same. In addition, market structure, seasonal effects as well as shock events were found to only affect the prices of small ruminants. The report presents preliminary recommendations for public and private sectors, with some predicated on further study.